Skills for sustainable development: transforming vocational education and training beyond 2015 - McGrath, Simon; Powell, Lesley (Elsevier, 2016)
There have been recent calls to transform VET and to transform development. This double call leads us to ask: how can skills development best support development that is sustainable for individuals, communities and the planet, whilst promoting social justice and poverty reduction? In considering this question we critique the idea of green skills for the green economy as being inadequate for achieving a transformed and transformative VET that shifts the target from economic growth to the well-being of individuals, and that enables vocational education to play a role in challenging and transforming society and work. Rather, we argue that we must see human development and sustainable development as inseparable, and plan and evaluate VET for its contribution to these. Such an approach must be grounded in a view of work, and hence skills for work, that is decent, life-enhancing, solidaristic, environmentally-sensitive and intergenerationally-aware. It must confront the reality that much current VET is complicit in preparing people for work that lacks some or all of these characteristics. It must be concerned with poverty, inequality and injustice and contribute to their eradication. It must be supportive of individuals’ agency, whilst also reflecting a careful reading of the structures that too often constrain them. In doing all this it must minimise the costs and risks of any transformation for the poor and seek to lock them into better individual and collective lives, not out of them. Finally, it must transform skills, work and the world in ways that are truly sustainable of the people of today but also those who are to inhabit the earth tomorrow.